2014
DOI: 10.1186/1476-4598-13-18
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β-induced activation of p38 promotes metastasis in gastric adenocarcinoma via upregulation of AP-1/c-fos, MMP2 and MMP9

Abstract: BackgroundInterleukin-1β (IL-1β) has been implicated in the progression of gastric adenocarcinoma (GA); however, the molecular mechanisms of action of IL-1β in GA are poorly characterized. P38 and JNK are the major MAPK family members that regulate IL-1β signaling pathways. Here, we investigated the role of both p38 and JNK in IL-1β-induced GA cell migration, invasion and metastatic potential.MethodsThe effects of IL-1β-induced p38 and JNK activation in GA cells were determined using in vitro Transwell migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 36 publications
7
82
0
Order By: Relevance
“…Numerous studies have demonstrated that extracellular MMP-2 and MMP-9 are overexpressed in various types of cancer (13)(14)(15). As demonstrated in Fig.…”
Section: Mir-524-5p Transfection Attenuates Cell Invasion By Inhibitimentioning
confidence: 92%
“…Numerous studies have demonstrated that extracellular MMP-2 and MMP-9 are overexpressed in various types of cancer (13)(14)(15). As demonstrated in Fig.…”
Section: Mir-524-5p Transfection Attenuates Cell Invasion By Inhibitimentioning
confidence: 92%
“…Due to its multifunctional role, the underlying mechanism allowing IL-1β to promote tumor growth and metastasis may consist of various signaling pathways, including inducing the expression of p38, c-Jun N-terminal kinase, matrix metalloproteinases, vascular endothelial growth factor, basic fibroblast growth factor, IL-8 and transforming growth factor-β that are required for tumorigenesis and metastasis (28)(29)(30)(31)(32)(33)(34). Previous studies have reported that IL-1β is able to regulate the epithelial-to-mesenchymal (EMT) transition by activating zinc finger E-box-binding homeobox 1 or stabilizing Snail expression to promote colon cancer formation (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…As extracellular zinc-dependent endopeptidases, they can degrade the basement membrane Unique Aspects of Anti-cancer Drug Developmentand ECM and thus play an important role in the migration and invasion of cancers. There are 23 members in MMPs family, among which MMP-2 and MMP-9 are considered to be the key enzymes and play crucial roles in cancer metastasis [39,40]. The activities of MMPs are finely mediated by tissue inhibitors of metalloproteinases (TIMPs) via their non-covalent binding to the active zinc-binding sites of MMPs [41].…”
Section: Suppression Of Proteases Expressionmentioning
confidence: 99%